Immunogenicity and immune memory of a nonadjuvanted quadrivalent meningococcal glycoconjugate vaccine in infants. - Perrett, K; Snape, MD; Ford, K; John, T; Yu, L; Langley, J; McNeil, S; Dull, P; Ceddia, F; Anemona, A; Halperin, SA; Dobson, S; et al. (2009)
BACKGROUND: The highest rate of invasive meningococcal disease is among children under 2 years of age. There is currently no licensed quadrivalent (serogroups A, C, W-135, and Y) meningococcal glycoconjugate vaccine approved for infants. We evaluated the immunogenicity and reactogenicity of a novel quadrivalent nonadjuvanted meningococcal glycoconjugate vaccine (MenACWY-CRM) in healthy infants. METHODS: One hundred eighty infants (90 in Canada and 90 in the United Kingdom) received 2 doses of MenACWY-CRM at 2 and 4 months of age administered concomitantly with routine infant vaccines. At 12 months of age, the Canadian infants received either MenACWY-CRM or a reduced dose of a licensed meningococcal polysaccharide vaccine. In the United Kingdom, all infants received a further dose of MenACWY-CRM. The serological marker of protection was a titer of > or =1:4 using a serum bactericidal assay with human complement (hSBA). RESULTS: Two doses of MenACWY-CRM induced hSBA titers > or =1:4 in 57% (95% confidence interval [CI]: 45-67) and 50% (95% CI: 38-62) of infants against serogroup A in Canada and the United Kingdom, respectively, 93% (95% CI: 85-97) and 86% (95% CI: 46-93) against serogroup C, 95% (95% CI: 87-99) and 82% (95% CI: 71-90) against serogroup W-135, and 91% (95% CI: 82-96) and 74% (95% CI: 63-83) against serogroup Y. After a booster dose of MenACWY-CRM at 12 months, at least 94% of participants achieved hSBA titers > or =1:4 against each of the serogroups C, W-135, and Y and more than 79% against serogroup A. The vaccine was well tolerated. CONCLUSIONS: The nonadjuvanted MenACWY-CRM is immunogenic and well tolerated in infancy and could provide broad protection against meningococcal disease in this vulnerable age group.